First-in-human study of AMG 820, a monoclonal anti-colony-stimulating factor 1 receptor antibody, in patients with advanced solid tumors - Papadopoulos, Kyriakos P.; Nagorsen, Dirk (Clinical cancer research, 2017)
Purpose: Binding of colony-stimulating factor 1 (CSF1) ligand to the CSF1 receptor (CSF1R) regulates survival of tumor-associated macrophages, which generally promote an immunosuppressive tumor microenvironment. AMG 820 is an investigational, fully human CSF1R antibody that inhibits binding of the ligands CSF1 and IL34 and subsequent ligand-mediated receptor activation. This first-in-human phase I study evaluated the safety, pharmacokinetics, pharmacodynamics, and antitumor activity of AMG 820. Experimental Design: Adult patients with relapsed or refractory advanced solid tumors received intravenous AMG 820 0.5 mg/kg once weekly or 1.5 to 20 mg/kg every 2 weeks until disease progression, adverse event (AE), or consent withdrawal. Results: Twenty-five patients received ≥1 dose of AMG 820. AMG 820 was tolerated up to 20 mg/kg; the MTD was not reached. One dose-limiting toxicity was observed (20 mg/kg; nonreversible grade 3 deafness). Most patients (76%) had treatment-related AEs; the most common were periorbital edema (44%), increased aspartate aminotransferase (AST; 28%), fatigue (24%), nausea (16%), increased blood alkaline phosphatase (12%), and blurred vision (12%). No patients had serious or fatal treatment-related AEs; 28% had grade ≥3 treatment-related AEs. Grade 3 AST elevations resolved when treatment was withheld. AMG 820 showed linear pharmacokinetics, with minimal accumulation (<2-fold) after repeated dosing. Pharmacodynamic increases in serum CSF1 concentrations and reduced numbers of skin macrophages were observed. Best response was stable disease in 8 patients (32%). Conclusions: AMG 820 was tolerated with manageable toxicities up to 20 mg/kg every 2 weeks. Pharmacodynamic response was demonstrated, and limited antitumor activity was observed.